Improving Employee Performance Through the Implementation of Individual Behavior as an Effort to Create an Organization with Character - Allyya Saputra (International Journal of Integrated Science and Technology, 2024)
Because of our individuality and diversity, people interact socially with one another. Human behavior within an organization has the power to shape its trajectory, meaning that individual actions have an impact on organizational behavior, which in turn has an impact on an organization's objectives. The author carried out this investigation for this reason. Finding out how individual behavior affects worker performance at PT. PLN Distribution for Greater Jakarta Area is the aim of this study. This study employs a quantitative descriptive methodology, utilizing questionnaire distribution and library data gathering approaches. Using basic linear regression data analysis techniques, 62 employees of PT. PLN Distribution for the Greater Jakarta Area were included in this study, which employed a saturation sampling strategy. The findings of this study indicate that employee performance at PT. PLN Distribution for Greater Jakarta Area is somewhat influenced by individual behavior. It is intended that this study's findings will aid in future investigations.